O instrumento da logística reversa de resíduos eletroeletrônicos no contexto da obsolescência programada e percebida: um olhar a partir da cidade de Santa Maria/RS - Mota, Luiza Rosso (2014)
This study is based on the Law 12.305/2010 (National politics on Solid Waste), which has progressed in in the field of sustainability, by transmitting a strong educational and awareness value. However, the increasing demand and offer of new technologies has caused in the population a big and increasing desire for consumption. In this sense, the objective of the research came to life, through the Law nº 12.305/2010, from the extension of the instrument in the reverse logistics of the consumer electronics in face of the consuming society and the capitalism market, both agents that use the planned obsolescence and perceived in spite of environmental balance. The central question proposed to be answered is presented in the following form: aware the ecological caos created/caused by the consuming society and the capitalist market, which incorporate the practice of planned obsolescence and perceived, it is asked if the reverse logistics instrument, brought by the Law that set up the National politics on Solid Waste, is it enough to strike/reduce the excess of consumer electronics surplus? Bringing to the real case, what is the situation of the consumer electronics waste in the city of Santa Maria/RS? The approach method utilized was the dialect. The theoretical framework presents itself from a base critical theory Zigmunt Baumam and Enrique Leff. The procedure method adopted was the case study, and the metodological instrument to data collection was the interview guidelines technic. It was studied, iniatialy, the consuming society and the capitalist market, emphasizing the planned obsolescence strategies programmed and perceived, and the cultural aspect tied to the consum; later, it was made a counterpoint in face of the National politics on Solid Waste and their main directives, explaining the collectors of recyclable material situation, the post-consumer responsibility and the shared liability, and contextualizing the reverse logistics instrument regarding the consumer electronics waste and, finaly, it was presented the counterpoint through the situation of the consumer electronics waste in the city of Santa Maria/RS. In the end, it was observed that the reverse logistics of the consumer electronics waste was not enough to strike or reduce the exceeding of consumer electronics waste, only contributes to the reducing the generation of these waste, in a minor percentage, because the planned obsolescence strategies and perceived practice by the market prevail in spite of the environment preservation and protection. There is a long road to go in the city of Santa Maria to reduce the distance between text (of law) and context (environmental reality) and to reach the desired minimum in the environmental related questions, with respect to consumer electronics waste.